Zlomi končnega dela koželjnice - Kogovšek, Urška (Medicinski razgledi, 2002)
Fractures of the distal end of the radius are the most common fractures in humans. Variants of the type of fracture and associated injuries are numerous,depending on the mechanism of injury, amount of energy absorbed and bone quality. It is commonly accepted that extra-articular anatomy and joint congruency, along with ligamentous integrity, needs to be restored to obtain agood functional result. Fractures of the distal end of the radius are mainly treated conservatively. Complications can generally be avoided with adequate treatment, patient monitoring and appropriate rehabilitation.
Keywords: Colles' fracture; Collesov zlom; Diagnosis; Zlom, fiksacija; Therapy; kosti; Classification; zlomi; Fracture fixation; koželjnica; zdravljenje; fiksacija